2011
DOI: 10.1158/1535-7163.mct-10-0669
|View full text |Cite
|
Sign up to set email alerts
|

Spliceosome-Mediated RNA Trans-Splicing Facilitates Targeted Delivery of Suicide Genes to Cancer Cells

Abstract: Patients suffering from recessive dystrophic epidermolysis bullosa (RDEB), a hereditary blistering disease of epithelia, show susceptibility to develop highly aggressive squamous cell carcinoma (SCC). Tumors metastasize early and are associated with mortality in the 30th-40th years of life in this patient group. So far, no adequate therapy is available for RDEB SCC. An approach is suicide gene therapy, in which a cell deathinducing agent is introduced to cancer cells. However, lack of specificity has constrain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…In the study by Gruber C. et al 87 the efficiency of 3` pre-trans-splicing molecules (PTM) was investigated and high efficiency was observed against highly malignant tumors. In the study by Di Stasi et al 88, the inducible caspase 9 (iCasp9) gene was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Gruber C. et al 87 the efficiency of 3` pre-trans-splicing molecules (PTM) was investigated and high efficiency was observed against highly malignant tumors. In the study by Di Stasi et al 88, the inducible caspase 9 (iCasp9) gene was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has the ability to replace a tumor-specific transcript with one encoding a cell death-inducing peptide/toxin. The group of Gruber C et al [96] investigated the efficiency of 3′ pre-trans-splicing molecules (PTM) and the results indicated that this method is efficient against highly malignant tumors. Another novel suicide gene therapy system was developed by Di Stasi et al [97].…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastases in prostate cancer are more likely to express MET than other soft tissue metastases 10. Preclinical studies in prostate cancer xenografts reported responses to cabozantinib therapy in nude mouse tibia (minimal bone lesions seen) as compared with development of multiple osteoblastic and osteolytic lesions in vehicle-treated controls 20. It is hypothesized that the osteoclast differentiation induced by cabozantinib may be responsible for the bone scan responses seen; however, the exact mechanism via which this occurs is unknown at present 20.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Preclinical studies in prostate cancer xenografts reported responses to cabozantinib therapy in nude mouse tibia (minimal bone lesions seen) as compared with development of multiple osteoblastic and osteolytic lesions in vehicle-treated controls 20. It is hypothesized that the osteoclast differentiation induced by cabozantinib may be responsible for the bone scan responses seen; however, the exact mechanism via which this occurs is unknown at present 20. Treatment with cabozantinib appeared to decelerate both osteoblastic and osteolytic progression of prostate xenograft tumors in bone.…”
Section: Mechanism Of Actionmentioning
confidence: 99%